Analysis of the Professional Management of Learing Community (PLC) in Improving Teachers' Pedagogic Competence (A case study of the 1st Grade Teacher in South Bend) - A. Hafid Munandar; Leli Nurlaeli; Suharyanto H Soro; Dinny Mardiana (Civiliza Publishing, Indonesia., 2025)
The management of the Professional Learning Community (PLC) and its impact on improving the pedagogic competence of elementary school teachers is still low. This is one of the causes of the quality of learning. The purpose of this research is to find professional management of the learning community towards improving teachers' pedagogic competence. The researcher uses a case study approach. Data were collected through observation methods, in-depth interviews, and documentation studies. The data analysis technique uses an interactive model that includes data condensation, data presentation, and conclusion drawn. The results of the study show that (1) Professional Management of Learning Community at SDN 1 Nagri Kidul is carried out through a weekly reflection cycle and sharing of best practices that are integrated into the school schedule; (2) The implementation of the Professional Learning Community significantly improves teachers' ability to design differentiated learning and manage authentic assessments. In conclusion, the structured management of the Professional Learning Community is effective in transforming teachers' pedagogic competencies from individualistic to collective work patterns.